Ethical considerations on in vitro fertilization technologies in Bangladesh - Islam, Sharmin; Nordin, Rusli Bin; Mohd, Hanapi Bin (Bangladesh Journal of Medical Science, 2013)
This paper aims to address ethical issues related to the assisted reproductive technology method in vitro fertilization (IVF) from the Islamic Shar?ah. This review reflects that the Islamic ethical viewpoint IVF is rational, comprehensive, and aims at the greatest good of mankind. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 121-128 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14938